ANALYSIS TERMINOLOGICAL APPARATUS SERVICES HOUSING AND COMMUNAL SERVICES - T. Skoda (Модернизация, инновация, развитие, 2016)
This paper presents an analysis of regulatory documents for the presence of each other and compliance with the basic concepts of the field of housing and communal services "housing and communal services", "public infrastructure" and "organization of public utilities." The results showed that at the moment there is no clear and unambiguous understanding of any of the concepts in question, resulting in signifi cantly complicates the process of state regulation of public utilities, the purpose of which is speedy modernization and improvement of its efficiency.